Don't Worry: How to Beat the Seven Anxieties of Life - Miller, Douglas (UK Pierson Prentice Hall, 2007)
We live in an era of fear and paranoia. Insomnia, depression and anxiety related illness is on the increase. What if we could eliminate the anxiety in our lives? What if we could face the future without fear of the unknown? Free yourself from anxiety, live your life to the full and exploit the possibilities of a life without irrational worry. Know yourself and understand what causes your anxiety Understand how anxiety in your life holds you back Learn how to mitigate against the anxiety you feel Learn and implement strategies that will reduce anxiety Discover steps that can be taken to reduce stress and anxiety at work Review progress and learn ways to further improve
Age Group: Adult
Keywords: Psychology; Self Help; Motivation; Mental health